Gladiolus aladagensis (Iridaceae), a new species from Turkey - Sağiroğlu, Mehmet; Eker İsmai̇l (Phytotaxa, 2021)
Gladiolus aladagensis is described and illustrated as a new species from Bolu province in Northwestern Anatolia, Turkey. Gladiolus aladagensis is morphologically close to G. italicus and G. kotschyanus. In this study, the diagnostic morphological features, distribution, conservation status, habitat and ecological characteristics of the new species are discussed. Micromorphological characteristics of G. aladagensis, G. italicus and G. kotschyanus seeds are also examined and compared using LM and SEM analyses. In addition, a new diagnostic key is given for all species of Gladiolus in Turkey.